It is time to balance communitarianism and individualism in South African medical education - L Campbell; A Ross; R MacGregor (South African Medical Association, 2015)
To the Editor: Recent well-meaning global and South African (SA) reforms in medical education primarily consider an agenda of social accountability. We are concerned that this approach may be the result of an excessive focus on the purpose of education to meet community needs (communitarianism) at the expense of the purpose of education to meet individual learner’s needs (individualism). If communitarianism and individualism are viewed as being at the opposite ends of a pendulum swing, we believe the pendulum is currently swinging too far away from individualism towards communitarianism, and that there should be a balance between these two.